The Influence of Migraine on Driving: Current Understanding, Future Directions, and Potential Implications of Findings. Issue 1 (2nd December 2019) - Tepper, Stewart J.; Silberstein, Stephen D.; Rosen, Noah L.; Lipton, Richard B.; Dennehy, Ellen B.; Dowsett, Sherie A.; Doty, Erin
Abstract : Objective: To review the published findings relevant to migraine and driving performance, with an intent to encourage discussion on research which may broaden understanding in this area and help educate healthcare providers and their patients. Background: Motor vehicle crashes result in more than 35, 000 deaths and more than 2 million injuries annually in the United States. Migraine is one of the most prevalent diseases in the world, and many symptoms associated with migraine attacks have the potential to negatively influence driving ability. Methods: We reviewed the published findings related to migraine and driving performance. Study findings relevant to symptoms of migraine and their potential effect on driving were also reviewed. This required a more expansive exploration of the literature beyond migraine, for example, review of the literature relating to the effect of pain, sleepiness, visual disturbances, or vertigo on driving. Finally, the potential effects of treatment for migraine on driving were reviewed. Results: Literature on the effect of migraine on driving performance is sparse and, in general published studies on the topic have a number of limitations. Based on review of the literature pertaining to other disorders, it seems feasible that some symptoms occurring as part of the migraine attack could impact driving performance, although formal study in this area is lacking. Many of the approved treatments for migraine have the potential to impact driving, yet this has not been specifically studied, and the extent to which these risks are communicated to patients is not clear. Conclusion: The impact of migraine on driving performance has been largely neglected, with few studies specifically designed to address the topic, and relevant studies were generally small with limited control of confounders. This area requires more focus, given a potential for impact on road safety.